Saccharification of alkali pretreated agroresidues to fermentable sugars by crude enzymes of cellulolytic fungi - Shankarappa, Thyavanahally Hanumaiah; Geeta, Gurunath Shirnalli; Manju, Mudigere Javaraiah; Patil, Chandragouda Rudragouda; Vamadevaiah, Hirematha; Jagadeesh, Kavi Shivalingappa (Asian Journal of Biological and Life Sciences, 2015)
Five agro-residues viz. sugarcane bagasse, sugarcane tops, sugarcane trash, corn husk and corn stover were alkali pretreated using 3.0% NaOH for 8 hours under ambient condition and then autoclaved at 1210C, 15 lbs pressure for 1h. The pretreated residues were subjected for saccharification using crude enzymes of four proven cellulolytic fungi at 10, 20 and 30 FPU per gram substrate. The release of reducing sugars as influenced by various concentrations of crude cellulase enzymes indicated that the treatment of 20U g-1 was optimum for all the crude enzyme extracts of different fungi studied. The crude enzyme extract of Trichoderma reesei when used at 20 U g-1 showed the significantly superior amounts of release of reducing sugars and per cent saccharification respectively in sugarcane bagasse (477.45 mg g-1 and 67.88%), sugarcane tops (428.68 mg g-1 and 62.94%), sugarcane trash (437.45 mg g-1 and 64.22%), corn husk (411.26 mg g-1 and 59.70%) and in corn stover (421.83 mg g-1 and 61.32%).
Keywords: Agroresidues; Cellulolytic fungi; Crude enzyme; Saccharification